Simulation study of ultra-compact microstrip UWB bandpass filter with wide stopband using dgs based lowpass filter - Sahu B.; Singh S.; Meshram M.K.; Singh S.P. (My University, 2025)
An ultra-compact ultra-wideband (UWB) bandpass filter (BPF) with good selectivity and wide stopband is proposed in this paper. Use of modified multimode resonator results in small filter size of 14 mm× 5.9 mm, whereas U-shaped defected ground structure (UDGS) based lowpass filter (LPF) provides wide stopband. The LPF structure is designed using four nonuniform configurations of DGS units along with a 50 Ω microstrip line. Each DGS unit is formed by cascading three isosceles UDGSs and analyzed in terms of an equivalent circuit model. The proposed filter has simulated passband (3-dB bandwidth) frequency range 3-11 GHz with wide stopband: attenuation better than 40 dB and 25 dB over the frequency ranges 11.7-20.5 GHz and 11.2 GHz-30 GHz respectively. © 2017 IEEE.